Research progresses in technological innovation and integration of agricultural engineering - Ming, Zhu; Xinqun, Zhou; Zhifen, Zhai (International Journal of Agricultural and Biological Engineering, 2016)
Abstract: Based on the technical characteristics of agricultural engineering, this research developed a theoretical system and methodology on the integration of agricultural engineering technology by studying the classification of constituent technologies, technological evaluation and integration, and optimization of agricultural engineering patterns. Thirty-two integrated agricultural engineering patterns are proposed according to the methodology for different regions with different local industry backgrounds, operating scales and objects. This research provides a solid foundation for the study of the agricultural engineering technical scheme, patterns and construction standards, which can help to provide a comprehensive solution to problems relevant to modern agriculture.Keywords: agricultural engineering, technology innovation, technology integration, technology classification, patternsDOI: 10.3965/j.ijabe.20160906.2440Citation: Zhu M, Zhou X Q, Zhai Z F. Research progresses in technological innovation and integration of agricultural engineering. Int J Agric & Biol Eng, 2016; 9(6): 1－9.